Reduced-order model prediction of far-field mixing noise from internally-notched nozzles - de Souza, Francisco J.; Lawrence, Jack; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
This work presents a numerical investigation of the effect of internal notches on the reduction of jet mixing noise from round nozzles. The baseline jet is produced by the University of Southampton’s Doak Laboratory 40mm-diameter convergent, round nozzle. Numerical predictions of mixing noise for both round and internally-notched nozzles are conducted using a Generalized Acoustic Analogy that relies on Reynolds-Averaged Navier-Stokes (RANS) solutions of the nozzle flows, particularly the one proposed by Leib and Bridges. In this method, the RANS variables of interest, including mean axial velocity, Mach number, density, turbulence kinetic energy, and its dissipation rate, are interpolated onto a cylindrical structured grid suitable for aeroacoustic calculations. Subsequently, the respective Green’s function and a hybrid spectral-time source model are computed, and power spectral densities at various polar and azimuthal angles are predicted. Comparison between predictions and experiments demonstrates good qualitative agreement for both nozzles, although the inversion in trends at certain Strouhal numbers is not captured by the numerical model. Additionally, the significance of the numerical scheme’s order employed to solve the adjoint Green’s function is evaluated. To elucidate the noise reduction attributed to internal notches, distributions of turbulent kinetic energy are analyzed at different azimuthal cross-sections.